Legal features and content of “the labour migrant" in russian administrative law - O. V. Nemtshenko (MGIMO University Press, 2012)
The article reviews in system the key notion of “the labour migrant” in the sphere of employment abroad. The article contains legal features, content and practical application of the labour migrant’s legislation. The author concludes about the public importance of migrant’s institution and about the necessity of proper legal regulation in the scope.